Boosting open-label placebo effects in acute induced pain in healthy adults (BOLPAP-study): study protocol of a randomized controlled trial - de Leeuw, Matthijs; Laager, Mirjam; Gaab, Jens; Ruppen, Wilhelm; Schneider, Tobias (Frontiers in Medicine, 2024)
Introduction: Pain is a highly prevalent symptom in the hospital setting, but treatment options remain limited. Harnessing the placebo effect in an ethical manner could provide a new possibility to reduce pain in clinical practice. So called open-label placebos (OLP) have been shown to elicit significant effects in reducing acute pain. But, before implementation, more knowledge concerning the properties of OLPs is needed. This study aims to assess the duration of analgesic effects from OLP and to determine the possibility of boosting such effects. Methods and Analysis: This is the protocol of an ongoing (first patient enrolled in March 2023) single-site randomized trial investigating OLPs in two parts (i.e., substudies). In both parts, pain will be induced in healthy adults using an intradermal electrical stimulation model. Participants in Part 1 will have two study visits: An interventional visit with one OLP injection accompanied by an evidence-based treatment rationale and a control visit with no treatment. For Part 2, participants will be randomized into three groups: 1.) A fixed-time “Booster” group including one single repetition of the OLP injection at a fixed time point, 2.) an on-demand “Booster” group including one single repetition of the OLP injection on-demand, and 3.) a control group who will receive just one OLP injection. Differences in pain ratings over time (using the Numeric Rating Scale) will be analyzed with several two-sample t-tests. The time point for a fixed-time “Booster” in Part 2 will be derived from Part 1 with additional statistical tools such as a broken-stick mixed-effect model. Discussion: This study aims to further characterize the analgesic effects of OLPs. In doing so, it will provide valuable information needed for later implementation of OLPs in clinical practice, where they could play a role in multimodal analgesic concepts. Ethics and Dissemination: The “Ethikkommission Nordwest- und Zentralschweiz” (BASEC 2023-00296) approved the study protocol. Results of the analysis will be submitted for publication in a peer-reviewed journal. Clinical Trial Registration: This study is registered at ClinicalTrials.gov (NCT05819476) and is listed in the Swiss National Registry at kofam.ch (SNCTP000005470).